Radiological diagnostic dilemma in a child with small aggressive facial mass, time to increase the differentials: an inflammatory myofibroblastic tumour - Fawzy, Waleed Mohamed Samy (BMJ Case Rep, 2020)
A 5-year-old girl with left facial swelling in the medial maxillary region close to the nasal ala was brought by her parents to our head and neck clinic. They have visited other doctors for similar presentation in the last 6 months, which started as redness and swelling, with occasional epiphora. The redness resolved after medical treatment, with slight regression of swelling, although it did not disappear. CT and MRI showed a locally aggressive, small enhancing soft tissue mass involving the left anteromedial maxillary wall, the nasal bone and the orbital floor. The mass involved the bony course of the nasolacrimal duct, which was the aetiology of the epiphora. The head and neck team performed an incisional biopsy through a sublabial approach. Concurrently, a nasolacrimal duct stent was inserted by an ophthalmologist. Histopathology was consistent with inflammatory myofibroblastic tumour with positive stains for CD68, CD163 and anaplastic lymphoma kinase-1. The tumour was excised and presently the patient is on periodic follow-up with head and neck and ophthalmology clinics.